The association of dietary insulin load and dietary insulin index with body composition among professional soccer players and referees - Beba, M.; Gholizadeh, M.; Sharifi, M.; Seifbarghi, T.; Djafarian, K. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background There has been limited research undertaken about the association of dietary insulin load (DIL) and dietary insulin index (DII) with body composition in non-athletic adults, however, to the best of our knowledge No previous study has investigated such an association in an athletic population.